The Effect of Reporting of Exchange Rate Losses on the Stock Market Reaction - Grahita Chandrarin, Michae. G Tearney (IAIkap, 2000)
In their seminal paper, Ball and Brwon (1968) documented a positive statistical association between earning surprises and stock return around an earnings announcement. They concluded that earnings conveyed useful information on the market. However the question of wheteher the exchage rate loss. as a component of earnings affects the stock market has never been answered yet. Yhe purpose of this paper is to examine the effect of reporting of exchange rate losses on the stock market. Empirical model model is estimated using OLS and multiple regression is used to analyze the relationship between exchange rate loss and stock price. A sample of 106 companies is devided into group 1 (companies with exchange rate loss) and group 2 (companies without exchange rate loss). All of the data are derived from COMPUSTAT tape for the year 1995-1996. with Standard and Poor 500 category. The results of this study support the shypothesis that there is a correlation between reportingof exchange rate losses and stock price. Thus the stock price rsponds exchange rate loss reflexted in earnings.